Extent of the tetrodotoxin induced blockade examined by pupillary paralysis elicited by intracerebral injection of the drug - Zhuravin, I A; Bures, J (Experimental brain research, 1991)
Spatial extent and duration of the functional blockade elicited by intracerebral injection of tetrodotoxin (TTX) was examined in rats anesthetized with pentobarbital. Pupillary diameter was measured under dissecting microscope before and up to 24 h after injection of TTX (10 ng/l microliters saline) into or 1.0, 1.5 and 2.0 mm lateral from the Edinger-Westphal nucleus. TTX administration elicited mydriasis the latency of which was directly and amplitude indirectly proportional to the target-injection distance. The maximum mydriasis attained 3.4 mm, lasted 2 h and slowly decayed over subsequent 20 h. Impulse transmission and conduction was blocked in a spherical volume of tissue about 3 mm in diameter the development of which could be approximated by diffusion from an instantaneous point source. Completeness and full reversibility make the TTX block a convenient research tool.
Keywords: nervus oculomotorius; Male; tetrodotoxin; mikroinjekce; Brain; stereotaktické techniky; Pupil; mužské pohlaví; Oculomotor Nerve; Mydriasis; Stereotaxic Techniques; krysa rodu Rattus; Microinjections; Animals; zvířata; Rats; mozek; pupila; Tetrodotoxin; mydriáza